Utilizing Quizizz to Improve Conceptual Understanding in Tsaqafah 'Arabiyah among Undergraduate Students of the Arabic Language Education Program / Pemanfaatan Quizizz untuk Meningkatkan Pemahaman Konseptual Tsaqafah 'Arabiyyah pada Mahasiswa Program Studi Pendidikan Bahasa Arab - Rahmawati, Dini; Saidah, Nur; Nurhadi, Nurhadi; Setiyawan, Adhi (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
The development of educational technology requires learning innovations that are responsive to the characteristics of the digital generation, including in Tsaqafah 'Arabiyah learning, which is conceptual and often perceived as difficult by students. A common problem is the low level of students’ conceptual understanding, influenced by the abstract nature of the material and learning approaches that are still dominated by lectures and memorization. Therefore, the use of interactive learning media is needed to increase cognitive engagement and strengthen students’ comprehension more effectively. This study aims to examine the effectiveness of the Quizizz platform as a gamification-based learning medium in improving students’ conceptual understanding in the Tsaqafah 'Arabiyah learning. This research employed a quantitative approach using a pre-test–post-test design involving 20 third-semester students of the Arabic Language Education Study Program at UIN Sunan Kalijaga. Data were analyzed using a paired sample t-test and N-Gain calculation. The results show a significant improvement in students’ scores from 61.50 to 80.25, with t = -7.471 and p = 0.000. The average N-Gain value of 0.4627 indicates moderate effectiveness.Perkembangan teknologi pendidikan memerlukan inovasi pembelajaran yang responsif terhadap karakteristik generasi digital, termasuk dalam pembelajaran Tsaqafah 'Arabiyah yang bersifat konseptual dan sering dianggap sulit oleh siswa. Masalah umum yang sering muncul adalah rendahnya tingkat pemahaman konseptual siswa, yang dipengaruhi oleh sifat abstrak materi dan pendekatan pembelajaran yang masih didominasi oleh ceramah dan hafalan. Oleh karena itu, penggunaan media pembelajaran interaktif diperlukan untuk meningkatkan keterlibatan kognitif dan memperkuat pemahaman siswa secara lebih efektif. Penelitian ini bertujuan untuk menguji efektivitas platform Quizizz sebagai media pembelajaran berbasis gamifikasi dalam meningkatkan pemahaman konseptual siswa pada mata kuliah Tsaqafah 'Arabiyah. Penelitian ini menggunakan pendekatan kuantitatif dengan desain pre-test–post-test yang melibatkan 20 mahasiswa semester ketiga Program Studi Pendidikan Bahasa Arab di UIN Sunan Kalijaga. Data dianalisis menggunakan uji t sampel berpasangan dan perhitungan N-Gain. Hasil menunjukkan peningkatan signifikan pada skor siswa dari 61,50 menjadi 80,25, dengan t = -7,471 dan p = 0,000. Nilai rata-rata N-Gain sebesar 0,4627 menunjukkan efektivitas moderat.